PARAMETER ESTIMATION FOR THE MARXIAN OPTIMAL GROWTH MODEL - Atsushi Tazoe (World Review of Political Economy, 2011)
In this article, we conduct an empirical analysis of a model called the Marxian Optimal Growth Model proposed by Yamashita and Onishi (2002). Mathematically, the Yamashita-Onishi model is the same as the neoclassical optimal growth model. Therefore, if analysis is limited to the steady state in the Yamashita-Onishi model, it is possible to use the techniques of macroeconometrics based on the dynamic stochastic general equilibrium model developed in the field of mainstream macro-econometrics. Examination of the analysis results showed that most of the discrepancies between the model and data are explained by error terms. To a certain extent, this could have been foreseen from the unrealistic assumptions of the basic Yamashita-Onishi model, and the fact that it was confirmed through actual analysis is significant. In this article, we must also note the fact that, although a Bayesian estimation approach was used in the analysis, the posterior distribution of the parameters derived as a result of the analysis is strongly affected by the prior distribution. This trend is particularly striking due to the small number of data items in the macroeconomic field.